Petrología y evolución diagenética de las facies silicoclásticas del Grupo Sierras Bayas, Sistema de Tandilia, Argentina - Lucía E Gómez Peral; María Sol Raigemborn; Daniel G Poiré (Latin American Journal of Sedimentology and Basin Analysis, 2011)
El estudio de las características petrológicas y microfaciales de las unidades silicoclásticas marinas del Neoproterozoico del Grupo Sierras Bayas, (en orden estratigráfico ascendente: formaciones Villa Mónica, Cerro Largo y Olavarría), se presenta en este trabajo con la finalidad de evaluar la evolución e importancia de los controles producidos durante los regímenes eodiagenético, mesodiagenético y telodiagenético. En la sección basal de la Formación Villa Mónica (800-900 Ma) se reconoce entre los componentes producidos durante el régimen eodiagenético, la presencia de caolinita, esmectita, clorita, ópalo y/o chert, goethita y hematita. Durante la mesodiagénesis se originaron interestratificados de illita-esmectita (con alta proporción de illita ~70%), cementos cuarzosos y recristalización de cementos silíceos generados en el régimen eodiagenético. A mayores profundidades se habría favorecido el crecimiento autigénico de illita, formación de estilolitas y de contactos suturados, disolución y reemplazo de cementos cuarzosos por hematita y calcita, como así también se infiere la transformación de caolinita a illita. Esto último indica que la unidad habría alcanzado el equilibrio a profundidades de 5 km o mayores y temperaturas elevadas (>150ºC). Luego, esta unidad fue expuesta a la telodiagénesis, reflejado por la degradación de argilominerales, formación de caolinita y esmectita en los niveles pelíticos y por el desarrollo de una superficie cárstica en las dolomías del tope de la formación. La evolución de la diagénesis en las areniscas de la Formación Cerro Largo se inicia con productos de la eodiagénesis vinculada a un ambiente marino de condiciones reductoras con la formación de pirita, esmectita y glauconita. Luego, durante la mesodiagenésis el cemento predominante fue el cuarzoso, con fuente de sílice externa y la esmectita fue transformada en interestratificados de illita-esmectita (con moderada esmectita ~50-40%), sumado al crecimiento autigénico de illita. Tales evidencias permiten inferir que esta unidad habría alcanzado un régimen meosodiagenétco profundo (<4 km de profundidad y temperatura <120ºC), aunque menor que el observado en la unidad subyacente. La posterior exhumación de estas rocas favoreció las alteraciones telodiagenéticas como la caolinitización, formación de esmectita y degradación de los interestratificados de illita-esmectita. El cuarzo fue disuelto y reemplazado por una asociación de cementos de hematita-goethita-calcedonia, vinculados, desde el punto de vista diagenético, a condiciones subsuperficiales. En las pelitas de la Formación Olavarría los rasgos diagenéticos indican que las mismas fueron afectadas por una mesodiagénesis temprana, donde se destaca el crecimiento autigénico de illita en la matriz arcillosa. Se observa también la preservación de rasgos eodiagenéticos, como escasa deformación de la matriz, predominio de fábrica flotante (abierta), formación de concreciones de calcita de posible origen microbiano, concreciones estratales multiepisódicas de hematita y venillas de ópalo. Este estudio permite señalar la existencia de una marcada diferencia en el grado de enterramiento y modificación diagenética registrados en las facies silicoclásticas inferiores con respecto a las suprayacentes del Grupo Sierras Bayas, cuyo espesor total es actualmente inferior a los 200 m. Por lo tanto, se sugiere que la sección inferior habría sido exhumada y fuertemente erodada con la pérdida de parte del registro rocoso, por lo que la discordancia que las separa representaría un lapso temporal importante. The Neoproterozoic sedimentary sequences of the Tandilia System Basin are represented in the Olavarría area by interstratified shallow marine, silicoclastic and carbonate units comprising, from oldest to youngest, for the Villa Mónica, Cerro Largo and Olavarría formations of the Sierras Bayas Group (Fig. 1). These almost undeformed and unmetamorphosed siliciclastics sedimentary units allowed studying the different diagenetic regimes due to the preservation of postdepositional features and, also, of many depositional and eodiagenetic ones. In the study area de Sierras Bayas Group is composed of the Villa Mónica (conglomerates, sandstones, shales and dolostones), Cerro Largo (chert breccias, quartz-sandstones and siltstones), Olavarría (mudstones) and Loma Negra (limestones) Formations with a thickness up to 185 m (Figs. 2 and 3; Iñiguez, et al., 1989; Poiré, 1987a, 1993; Gómez Peral, 2008). The siliciclastics facies of the Sierras Bayas Group are composed of conglomerates, sandstones and mudstones, represented in the basal section of the Villa Mónica Formation and the Cerro Largo and Olavarría formations (Fig. 4). The objective of the present study was to reveal the sequence of diagenetic processes represented in the silicoclastic facies from a detailed petrological analysis. It included the recognition of the allogenic and authigenic components, the characterization of the diagenetic microfabrics (chemical and compactational), the definition of microfacies and the interpretation of the postdepositional burial history from the determination of paragenetic sequences. Besides, a revision of the classical depositional facies chart was performed. Considering that different factors may influence the diagenesis of sediments at different times during its evolution (Kantorowicz, 1985), the general controls on diagenesis include the depositional mineralogy, the depositional-water chemistry, the change in pore fluid composition, the inferred burial pressures and the temperatures and subaerial exposure. From the lithofacial analisys we remark the presence of some facies with potential glacial origin here described as laminated gravelly mudstone (Fig. 5; facies FGh) in the basal section of the Villa Mónica Formation and the "Colombo" diamictite (Fig. 6; Ds) in the base of the Cerro Largo Formation. Other interesting level is present in the base of the Olavarría Formation where we recognized an intraformational conglomerate (Fig. 6; facies MCh) likely associated with a volcanic arc affinity by geochemical data (Zimmerman et al., 2011). The quartz-arkosic facies of the lower section of the Villa Mónica Formation can be separated in three petrofacies according with its detrital mineralogy: i) subarkosic sandstones (arenites and wackes) at the base; ii) lithic and sublithic sandstones rich in polycrystalline quartz (arenites and wackes) in the middle part and iii) quartz sandstones in the upper section (Table 1 and Fig. 7). A detailed analysis of the microfacies allowed the interpretation of the interaction of diagenetic processes with sediments during an important geological time interval (Tables 2, 3 and Figs. 8, 9 and 10). In the same sense, the identification of diagenetic facies permitted the differentiation of sections of the succession characterized by different diagenetic modifications. Clay minerals were analyzed since illite crystallinity, identification of interestratified illite/smectite and its smectite proportion help to assess the relative depth of burial reached for these sedimentary rocks. The main detrital and authigenic components, as well as the definition of their microstructures, allowed identifying 25 microfacies in the silicoclastic section of the Villa Mónica Formation (Table 2) and the interpretation of the evolution of the processes occurred during the different diagenetic regimens. The eodiagenetic regime involved degradation of K-feldspars to kaolinite, smectite, cementation with opal and hematite, as the result of the interaction with meteoric waters between surface and shallow burial depths. Subsequently, basinal brines controlled the diagenetic evolution of the sandstones and resulted in the initial transformation of smectite into interestratified illite-smectite, precipitation of quartz overgrowths, and recrystallization of siliceous cements. During further burial the most important alterations included transformation of interestratified illite-smectite in ordered type (R1) containing 70-80% of illite in relation with authigenic growth of illite; scarce authigenic chlorite as replacement of biotite and amphibole, illitization of kaolinite (inferred), pervasive stylolitization added to the formation of sutured contact grains, and later with hematite replacements and late calcite cements. All these features indicate an equilibrium of the fluids with very deep burial and high temperatures (Fig. 11; > 5 km and >150ºC). An important uplift is registered related to a period of intense erosion and weathering with the generation of a karstic surface on top of dolostones of the Villa Mónica Formation which constitutes a telodiagenetic surface. This important unconformity was situated in 595 Ma according to paleomagnetic studies, (Rapallini et al., 2008) and was characterized by dedolomitization, intense dissolution and precipitation of goethite, hematite, chert and calcite, which produce a typical reddish to pink coloration (Gómez Peral, 2008). Sandstones of the Cerro Largo Formation were divided in two petrofacies (Table 1; Fig. 7); the quartzose lower one is mostly composed of monocrystalline quartz with low proportion of matrix (< 10%), very scarce policrystaline quartz, chert and mudstone intraclasts. The analysis of detrital and diagenetic mineralogy, and the different microstructures allowed the recognition of 5 microfacies (Table 3). The diagenetic evolution of this unit began with eodiagenetic processes related to the formation of euhedral pyrite, infiltration of smectite, authigenic glauconite and chert cementation. The most important mesodiagenetic modifications included quartz cementation, which complete the pore-filling, followed of partial dissolution of quartz and replacement by subhedral hematitic cement. Progressive burial drove the transformation of detrital and eodiagenetic smectite, first into poorly and then into better-ordered, mixed-layer illite/ smectite (I/S). In the Cerro Largo Formation the I/S reaches a low ordered (R0) containing near of 40-50% of illite, added to the authigenic generation of illite with crystallinity index typical of diagenetic zone. Furthermore, these features can be related to a middle-deep mesodiagenesis (Fig. 11; < 4 km and < 120°C). However, this process was restricted to intercalated mudstones with clayminerals. Sparse stylolites and tangential to planar grain contacts are the most conspicuous chemical compaction indicators. Uplift and incursion of meteoric waters constrained the telodiagenetic alterations including kaolinitization and smectite generation as well as degradation of mixed-layer illite/smectite which increment their smectite proportion. One prominent telodiagenetic products in this quartz-sandstones was the dissolution of quartz cements in presence of pervasive fluids and its replacement by hematite, goethite and chalcedony. In the mudstones levels the presence of a clay association of smectite, kaolinite and pyrofillite was related to an advanced argillic alteration due to possibly hydrothermal influence. One of the most important inferences was the recognition of different burial diagenetic histories in the siliciclastic units of the lower part of the Sierras Bayas Group (lower section if the Villa Mónica Formation) respect to the upper successions (Cerro Largo and Olavarría formations) which implies that the discordance on top of the Villa Mónica Formation could represent a long period of erosion and subaerial exposure.